The rational variability of all empty space by prime numbers - Cameron, Vinoo (International Journal of Applied Mathematical Research, 2013)
This mathematics manuscript has no conjecture, and the values of the half-line prime number are absolute and of simple pure mathematics by dual spiral cords that clearly spell out the distributive form of Prime numbers. The very clear half-line values for each prime numbers are made indirectly by using our continuous sieve of prime numbers ( Den otter/Hope research sieve) or any other risky prime sieve .Half-line values for each prime number are constant by an ascension order ( 19=16 for instance). This is also done directly using the quadratic base to derive the variability, and the values of sets are constant. We have shown the characteristics of Prime numbers genesis and distribution, by clear sublime mathematics, that no living mathematician can question as the values are absolutely clear and that this is the way the creator created the prime numbers Now the concepts of current mathematics with regards to prime numbers are passé and in the authors opinion they are convoluted. The orientation of prime number distribution of the curved spiral is “warped variable constant” by spiral sets of fixed prime number distribution. The coordinates are fixed at 1:3 and the spiral sets are fixed; the orientation is however twisted and warped from each position as shown herein. The coordinates of the Chan point prime numbers 5:7 (14:16) 19:23 are at the base and un-warped and this is evident topologically in any flat paper rendition of prime numbers, but after that the midline rotates by set orientation and topologically the spiral ascension has variable orientations but predictable dimension from any given point. This is the numbers theorem of space orientation, and dimension where all numbers represent their relationship to the half-line. Proof of this also is in the patent 1:3 diagram by topology shown below, and the “Chan point” by quadratic base and spiral orientation.